2008
DOI: 10.1038/jp.2008.81
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of domperidone on gastroesophageal reflux in newborns assessed by combined intraluminal impedance and pH monitoring

Abstract: Objective: Neonatal gastroesophageal reflux (GER) is primarily due to a transient motility disorder and characterized by a prevalence of weakly acid refluxes. Drug management, where necessary, must set out to reduce the number of refluxes besides correct their acidity. Prokinetics could be of assistance in this respect, though the evidence in favor of their efficacy and safety is still far from sufficient. In this randomized controlled study, the action of domperidone, a prokinetic antidopaminergic drug with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…(13) The reliability of MII/pH in detecting reflux events and its ability to characterize them according to duration, proximal extent and pH make this technique excellent for clinical research; it has already been used in newborns to assess the relationship between apnea of preterm and GER,(4), (17), (18) the effects of drugs (19), (20) During follow-up, GERD symptoms tended to disappear spontaneously, following a decay curve in which half of the patients were asymptomatic in the fifth month of age, and the vast majority were asymptomatic after the first year of life according with what was demonstrated in a previous prospective study. (22) Analysis of MII/pH variables demonstrated that, as already observed by other authors, in the first weeks of life the frequency of reflux events is physiologically high (2-4 reflux events/hour) and that weakly acidic reflux events are predominant.…”
Section: Discussionmentioning
confidence: 99%
“…(13) The reliability of MII/pH in detecting reflux events and its ability to characterize them according to duration, proximal extent and pH make this technique excellent for clinical research; it has already been used in newborns to assess the relationship between apnea of preterm and GER,(4), (17), (18) the effects of drugs (19), (20) During follow-up, GERD symptoms tended to disappear spontaneously, following a decay curve in which half of the patients were asymptomatic in the fifth month of age, and the vast majority were asymptomatic after the first year of life according with what was demonstrated in a previous prospective study. (22) Analysis of MII/pH variables demonstrated that, as already observed by other authors, in the first weeks of life the frequency of reflux events is physiologically high (2-4 reflux events/hour) and that weakly acidic reflux events are predominant.…”
Section: Discussionmentioning
confidence: 99%
“…The study of domperidone treatment at the dose of 0.3 mg/kg/dose in 13 newborns demonstrated no serious side effects. 2 However, Rocha et al 4 reported a QT prolongation in a 4-month-old infant receiving a high dose of 0.6 mg/kg three times a day. In addition, domperidone caused QT prolongation in patients who received concomitant treatment with ketoconazole.…”
Section: Introductionmentioning
confidence: 98%
“…Domperidone is a dopamine-2 receptor antagonist [1][2][3] and affects the chemoreceptor trigger zone on the 4 th ventricle outside the blood-brain barrier and the motor function of stomach and small intestine. In contrast to metoclopramide, domperidone does not cross the blood-brain barrier; therefore, the neurologic side effects, such as dystonic reaction, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…In a controlled study of 26 neonates, two doses of domperidone were given during a 24-h combined multichannel intraluminal impedance and pH study [ 10 ]. There was a paradoxical increase in the number of refl ux episodes, a decrease in refl ux duration, and no difference in the maximal proximal extent of refl ux or changes in the pH.…”
Section: Dopamine-2 (D2) Receptor Antagonists Domperidonementioning
confidence: 98%